PEMANFAATAN PANGAN LOKAL BERAS JAGUNG (Zea Mays L)PADA KONSUMSI PANGAN DI KABUPATEN MINAHASA SELATAN - Ansye S. Tangkilisan; Christine F. Mamuaja; Lexie P. Mamahit; Thelma D. Tuju (COCOS, 2013)
AbstractCorn is a commodity potential to be developed into an alternative staple food because corn production levels are quite large and also the nutritional content of corn in particular proteins and carbohydrates are not inferior to rice. This study aims to determine the consumer appetite for corn and rice consumption purchasing power of consumers to rice corn. The data obtained through the survey method through interviews with consumers households in District East Amurang, Amurang, and West Amurang in South Minahasa district and each taken 25 respondents. The results showed that on average each family consumes as much corn rice 2.29 liters per month and the average expenditure for the purchase of corn rice per family per month is Rp. 7886. The results also show that most members of the family (father, mother and child) like corn rice. This means that the demand for rice maize is consumed as a food ingredient is cooked with the rice paddy. Keywords: Local Food, Corn